Perkembangan Dan Perubahan Konstitusi Indonesia - Hendryan, Dery; Kartadinata, Andriansyah (VIVA THEMIS, 2025)
This research discussed about the development of the constitution Indonesia which has been determined since August 18 1945. The approach used in this research is juridic normative, while the source of data is secondary data. The result of this research indicates that the constitution Indonesia has ever been changed several times. It can be seen from UUD 1945, UUD RIS, UUDS 1950 and then turned back again to the UUD 1945, which has been approved for from times and it is valid until now on. The changeover of the constitution Indonesia is caused by internal and external factors. It is also influenced by the real condition of law political which brings the impact to the change of the constitutional system in Indonesia